2004
DOI: 10.7863/jum.2004.23.10.1327
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Nasal Bone Length in Euploid and Aneuploid Fetuses Between 11 and 20 Weeks' Gestation

Abstract: Nasal bone hypoplasia in the early second trimester identifies a cohort of fetuses at high risk for aneuploidy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
3
42
1
4
Order By: Relevance
“…Nazal kemiğin hipoplazisi ya da aplazisi Down Sendromu başta olmak üze- A B re anöploidi belirteci olarak kullanılmaktadır. Literatürde nazal kemik uzunluğunun normal değerlerini gösteren birçok çalışma vardır [27,28]. Cusick ve ark.…”
Section: Nazal Kemi̇k Aplazi̇si̇-hi̇poplazi̇si̇unclassified
“…Nazal kemiğin hipoplazisi ya da aplazisi Down Sendromu başta olmak üze- A B re anöploidi belirteci olarak kullanılmaktadır. Literatürde nazal kemik uzunluğunun normal değerlerini gösteren birçok çalışma vardır [27,28]. Cusick ve ark.…”
Section: Nazal Kemi̇k Aplazi̇si̇-hi̇poplazi̇si̇unclassified
“…As compared to other studies, mean values in each week of this study are higher, but closely matching Ozer et al, study and far from Cusick et al, study. 10,11 We suspect that these highly different values among populations are not solely explained by maternal ethnicity, but are also due to variation in technique such as including or excluding the relatively hypoechogenic ends of NB. 12 As NB increased linearly with CRL and gestational age in this study as in other studies.…”
Section: Prenasal Thickness (Pt) and Gestational Agementioning
confidence: 99%
“…In order to avoid false finding that the NB was either absent or shortened, the angle of the fetal nose was maintained between 45° and 135° [12,22]. The BPD was measured on the transverse axial section of the fetal head -which included the midline falx and the thalami symmetrically positioned on either side of the falx -from the outer edge of the nearer parietal bone to the inner edge of the more distant parietal bone whilst visua-lizing the septum pellucidum at one-third along the frontal-occipital distance.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Published data have shown that when comparing Down Syndrome fetuses with euploid fetuses, Down Syndrome fetuses were more frequently associated with NB hypoplasia [12][13][14][15]. Reviewing several past studies, in addition to discussing the relationship between nasal bone length (NBL) and gestational age or biparietal diameter (BPD), the BPD/NBL ratio ≥ 10 and ≥ 11 were proposed for the definitions of nasal bone hypoplasia in the second trimester [13,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%